MAXIM INFRINGEMENT OF CAPTAIN HADDOCK IN THE ADVENTURE OF TINTIN - Rudy Prasojo; Nababan Nababan; Djatmika Djatmika (Universitas Sebelas Maret, 2017)
Maxim infringement is one of non-observance maxim which occurs when the speaker has no intention to make an implicature because the speaker is incapable to speak clearly. Generally infringing stems from imperfect linguistic performance or from impaired linguistic performance. Objectives of this research is about maxim infringement brought by Captain Haddock in a comic series of The Adventure of Tintin. The researcher found that 80% of maxim infringement occured because Captain Haddock was under the influence of liquor and the rest occured when He was on critical situation betweeen life and death. The researcher found connection between maxim infringement and speech act theory, even supposing maxim infringement result in failure of the speaker in generating implicature. As conclusion, maxim infringement brought by the character of Captain Haddok shows that it happens mostly because the speaker temporaly has cognitive impairment to make an implicature caused by under influence of liquor and some critical situations.